Fly ash particulate reinforcement for property enhancement of PU foam core sandwich composites - Pareta, Ashish Singh (IIT(BHU) Varanasi, 2023)
Abstract is available in the content.
Keywords: Fly ash particulate reinforcement; property enhancement; PU foam; core sandwich composites